Crystal structure of tetrawickmanite, Mn(2+)Sn(4+)(OH)(6) - Lafuente, Barbara (International Union of Crystallography, 2015)

(untitled) (Acta Crystallogr E Crystallogr Commun)
The crystal structure of tetrawickmanite, ideally Mn(2+)Sn(4+)(OH)(6) [manganese(II) tin(IV) hexahydroxide], has been determined based on single-crystal X-ray diffraction data collected from a natural sample from Långban, Sweden. Tetrawickmanite belongs to the octahedral-framework group of hydroxide-perovskite minerals, described by the general formula BB’(OH)(6) with a perovskite derivative structure. The structure differs from that of an ABO(3) perovskite in that the A site is empty while each O atom is bonded to an H atom. The perovskite B-type cations split into ordered B and B′ sites, which are occupied by Mn(2+) and Sn(4+), respectively. Tetrawickmanite exhibits tetragonal symmetry and is topologically similar to its cubic polymorph, wickmanite. The tetrawickmanite structure is characterized by a framework of alternating corner-linked [Mn(2+)(OH)(6)] and [Sn(4+)(OH)(6)] octahedra, both with point-group symmetry -1. Four of the five distinct H atoms in the structure are statistically disordered. The vacant A site is in a cavity in the centre of a distorted cube formed by eight octahedra at the corners. However, the hydrogen-atom positions and their hydrogen bonds are not equivalent in every cavity, resulting in two distinct environments. One of the cavities contains a ring of four hydrogen bonds, similar to that found in wickmanite, while the other cavity is more distorted and forms crankshaft-type chains of hydrogen bonds, as previously proposed for tetragonal stottite, Fe(2+)Ge(4+)(OH)(6).